2004
DOI: 10.1152/ajpgi.00305.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acid secretion by the nonsteroidal anti-inflammatory drugs diclofenac and piroxicam in isolated gastric glands: analysis of a multifocal mechanism

Abstract: In nonstimulated rabbit gastric glands, acetylsalicylic acid (10-500 microM) and indomethacin (3-300 microM) did not significantly modify the basal rate of acid secretion, whereas diclofenac and piroxicam (10-1,000 microM each) caused a marked and dose-dependent inhibitory effect (EC(50) = 138 and 280 microM, respectively). In gastric glands stimulated by histamine (100 microM), diclofenac also reduced the rate of acid formation in a dose-dependent manner. In contrast, acetylsalicylic acid, indomethacin, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Increased gastric acid secretion is proposed as a primary, probable pathogenic mechanism of NSAID-induced gastric hemorrhages (Wallace, 2008). NSAIDs in vivo increase baseline and stimulated gastric acid secretion, and support the idea that gastric acid is involved with ulcer formation (Salvatella et al, 2004). In the present study, JZL184 significantly decreased gastric acid secretion in both basal and pentagastrin-stimulated conditions 3 h after JZL184 administration.…”
Section: Discussionsupporting
confidence: 59%
“…Increased gastric acid secretion is proposed as a primary, probable pathogenic mechanism of NSAID-induced gastric hemorrhages (Wallace, 2008). NSAIDs in vivo increase baseline and stimulated gastric acid secretion, and support the idea that gastric acid is involved with ulcer formation (Salvatella et al, 2004). In the present study, JZL184 significantly decreased gastric acid secretion in both basal and pentagastrin-stimulated conditions 3 h after JZL184 administration.…”
Section: Discussionsupporting
confidence: 59%
“…12 Of note, certain NSAIDs, such as diclofenac and piroxicam, while inhibiting prostaglandin synthesis also inhibit isolated gastric gland acid secretion by interacting with H + /K + -ATPase activity. 13 We and others have observed that NSAIDs stimulate basal acid secretion in vivo 7,10,11,14 and potentiate secretagogue-stimulated acid secretion in vitro and in vivo. 6,8,9,15,16 A rational approach to prevent ulcerogenesis is to suppress the production of gastric acid, either with histamine H 2 receptor antagonists or proton pump inhibitors.…”
Section: Introductionmentioning
confidence: 89%
“…In addition to the inhibition of prostaglandin synthesis, other changes may underlie NSAID‐induced gastrointestinal mucosal injury, including stimulation of gastric acid secretion, 6–11 suppression of duodenal bicarbonate secretion 7 and lack of adaptation to injury 12 . Of note, certain NSAIDs, such as diclofenac and piroxicam, while inhibiting prostaglandin synthesis also inhibit isolated gastric gland acid secretion by interacting with H + /K + ‐ATPase activity 13 . We and others have observed that NSAIDs stimulate basal acid secretion in vivo 7,10,11,14 and potentiate secretagogue‐stimulated acid secretion in vitro and in vivo 6,8,9,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro animal studies have demonstrated that aspirin and some NSAIDs such as indomethacin, piroxicam and naproxen may increase acid secretion that has been stimulated by histamine, dibutyryl cAMP or forskolin with no effect on basal acid secretion rate 18–22 . Salvetta et al 4 . demonstrated that the NSAIDs diclofenac and piroxicam reduced the rate of both basal and histamine‐stimulated acid in rabbit gastric glands.…”
Section: Discussionmentioning
confidence: 99%
“…With development of new NSAIDs and investigation of mechanism(s) of action, it has become evident that different NSAIDs may have different mechanisms of action on the gastroduodenal mucosa, explaining the observation that some NSAIDs are more damaging than others 4–7 . The conundrum faced by NSAID development revolves around the use of prostaglandins to decrease inflammation while coincidently inducing GI mucosal damage.…”
Section: Introductionmentioning
confidence: 99%